Adaptive Coverage Control for Dynamic Pattern Generation - Fungtammasan K. (2023)
This paper studies an adaptive coverage control problem for a system of multiple car-like mobile robots. The Centroidal Voronoi Tessellation (CVT) is applied to generate an optimal coverage configuration of the multi-agent system for a dynamic region. A function approximation technique based immersion and invariance (FATII) controller is proposed to drive the system to the generated optimal configuration while ensuring the output constraint. The stability of the proposed FATII controller is established and its validity is tested under experiments.